The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0189144
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of reaction knockouts to maximize succinate production by Actinobacillus succinogenes

Abstract: Succinate is a precursor of multiple commodity chemicals and bio-based succinate production is an active area of industrial bioengineering research. One of the most important microbial strains for bio-based production of succinate is the capnophilic gram-negative bacterium Actinobacillus succinogenes, which naturally produces succinate by a mixed-acid fermentative pathway. To engineer A. succinogenes to improve succinate yields during mixed acid fermentation, it is important to have a detailed understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Results from model predictions generated via flux balance analysis were in accordance with experimental data on mixed acid fermentation. 75 Elimination of metabolic pathways competing with succinic acid production and the incorporation of non-native metabolic pathways would lead to high succinic acid production with high yield and productivity. However, it has been demonstrated that the removal of competitive carbon pathways is insufficient to enhance carbon flux to succinic acid, although effective reduction in byproducts was observed in engineered strains.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Results from model predictions generated via flux balance analysis were in accordance with experimental data on mixed acid fermentation. 75 Elimination of metabolic pathways competing with succinic acid production and the incorporation of non-native metabolic pathways would lead to high succinic acid production with high yield and productivity. However, it has been demonstrated that the removal of competitive carbon pathways is insufficient to enhance carbon flux to succinic acid, although effective reduction in byproducts was observed in engineered strains.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Comprehensive carbon metabolism model (375 reactions) to analyze the metabolism and predict knockout strategies for maximum SA production with maintaining the cell growth 2018 [95] A. succinogenes Genome-scale metabolic model to evaluate the metabolic capability of the strain to produce SA under various conditions 2018 [30] Zymomonas mobilis Genome-scale metabolic model to characterize SA-producing capability and comparatively identify gene deletions for enhanced SA production 2018 [96] E. coli Optimization modeling to identify near-optimal knockout genes for the maximum production of SA 2020 [97] Aspergillus niger…”
Section: E Coli and A Succinogenesmentioning
confidence: 99%
“…Hence, the development of models with more inclusive and higher predictive power was needed. Nag et al developed an extended intermediate model that contained nucleic acid, amino acid, lipid and glycogen metabolisms in addition to the central carbon metabolism [95]. However, this model still did not explicitly incorporate all the known metabolic pathways of A. succinogenes to have a comprehensive understanding of the strain's metabolism.…”
Section: Attempts At Metabolic Modeling Of a Succinogenesmentioning
confidence: 99%
“…To elaborate the metabolic machinery of A. succinogenes clearly, 13 C metabolic flux analyses, flow calculation, several central carbon metabolism models, and the major biomass components models were used recently . Subsequently, several efficient expression methods like pLGZ920 plasmid and electroporation markerless knockout methods were proposed .…”
Section: Succinic Acid Production By Metabolically Engineered Strainsmentioning
confidence: 99%